DIGITAL TRANSFORMATION TO BUILD THE IMAGE OF RSU PAYANGAN: BRANDING STRATEGY IN THE DIGITAL ERA - Widnyani , Ni Made; Astitiani, Ni Luh Putu Surya; Rettobjaan, Vitalia Fina Carla; Richadinata, Kadek Riyan Putra; Aristayudha, A.A. Ngurah Bagus (Jurnal Abdimas Ilmiah Citra Bakti, 2024)
Digital transformation has revolutionized various sectors, including healthcare, where RSU Payangan recognizes the importance of adapting to digital marketing trends to strengthen its brand image and maintain competitiveness. This community service program aims to explore the effectiveness of digital marketing in building RSU Payangan’s image through intensive training and discussions with hospital management. The activity is designed to enhance management’s understanding of relevant digital marketing strategies in the contemporary era. The methods used include in-depth interviews to assess previously implemented marketing strategies, surveys on public perception of the hospital’s image, and evaluations of the effectiveness of past marketing strategies. The results indicate that the strategic application of digital marketing successfully increased public awareness of RSU Payangan’s healthcare services, accompanied by greater community engagement on digital platforms. Success indicators include improved management understanding of digital marketing, increased digital traffic, heightened community engagement on social media, and positive changes in public perception of RSU Payangan’s image. With positive feedback from training participants, this activity demonstrates that digital marketing is an effective tool to strengthen the hospital’s image amidst the increasingly competitive healthcare sector.